1972
DOI: 10.1136/oem.29.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism of shift and day workers: A study of six types of shift system in 29 organizations

Abstract: Taylor, P. J., Pocock, S. J., and Sergean, R. (1972).Brit. J. industr. Med.,29, 208-213. Absenteeism of shift and day workers. Previous evidence on the effects of shift work upon absence behaviour is conflicting, this being due in part to the variety of shift systems in use. A study is described in which absence records over two years were obtained for 965 matched pairs of shift and day workers from 29 organizations. Six types of shift system were involved, providing comprehensive coverage of shift work in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In this and other studies employees who worked for greater than 48 h per week were more likely to experience sickness absenteeism than those who did not [ 5 , 19 ]. This is true for employees who engaged in overtime work [ 20 ]. The reason could be that working above normal working hours would affect muscular activities and caused mental fatigue which might lead employees to increased risk of accidents.…”
Section: Discussionmentioning
confidence: 99%
“…In this and other studies employees who worked for greater than 48 h per week were more likely to experience sickness absenteeism than those who did not [ 5 , 19 ]. This is true for employees who engaged in overtime work [ 20 ]. The reason could be that working above normal working hours would affect muscular activities and caused mental fatigue which might lead employees to increased risk of accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Male gender and lower education levels are known to be main risk factors for workplace injury and work absence in many studies [41, 48, 49]. Similar to workers in other counties, Korean workers involved in a shift/night work schedule exhibited an increased risk of work absence [8, 5052]. Job type/title/occupation has been shown to be a gross risk category for injuries, sickness absence and health status [5356] [13].…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that long-time absence could be more prevalent among evening and night workers than among day workers, since evening and night work is not only suspected to cause shortterm sickness, but also severe and chronic diseases, such as cardiovascular diseases, cancer, and metabolic disturbances, as well as an increased risk of trauma and severity of trauma due to accidents (5,6). On the other hand, pioneer studies found that day workers had more sickness absence than shift workers in a chemical plant in Norway 7, and in 29 organizations in the United Kingdom (8,9). Some studies suggest that shift workers have either higher sickness absence rates or more or longer absences than day workers (10)(11)(12)(13).…”
mentioning
confidence: 99%